The Angelized Rabbis and the Rabbinized Angels. The Reworked Motif of the Angelic Progeny in the Babylonian Talmud (bShabb 112b) - Kosior, Wojciech (Verbum Vitae, 2023)
The myth of the fallen angels, as it is known from the intertestamental literature, narrates the story of the angels who break the divine law, marry earthly women, and beget malevolent hybrid progeny. The latter element of this narrative can be found in the Babylonian Talmud, where it is invested with new significance: these are the distinguished rabbis who are the heavenly messengers’ offspring. I start this paper by outlining the traces of the rabbis’ familiarity with the myth of the fallen angels and then move on to an analysis of the tradition about the angelic origins of the sages found in bShabb 112b. I offer that this passage should be read as exemplifying the practice of associating rabbis and angels that permeates the whole Babylonian Talmud. I base on two methodological paradigms: cognitive linguistics, which allows for the translation of this problem into two conceptual metaphors (SAGES ARE ANGELS and ANGELS ARE SAGES), and the Elyonim veTachtonim – a system of quantitative and qualitative analysis of the traditions involving supernatural entities, which permits to locate all the Talmudic passages utilizing these metaphors and to interpret their place in the broader conceptual network. The data show that the sages and rabbinized biblical figures are frequently juxtaposed with angels, and the main dimension of comparison is their intellectual proficiency. When it comes to the mapping of specific rabbinic competencies onto the angels, the most popular is the ability to engage in halakhic scrutiny and teaching. In sum, this presentation of the sages as angels can be taken as an expression of the sense of elitism entertained by the Babylonian sages and, as such, sheds additional light on the interpretation of the passage in bShabb 112b.